Natural convection heat transfer of a straight-fin heat sink - Meng, Xiangrui; Zhu, Jie; Wei, Xinli; Yan, Yuying (Elsevier, 2018)
The influence of mounting angle on heat dissipation performance of a heat sink under natural convection condition is investigated in this paper by numerical simulation and experimental test. It is found that the heat sink achieves the highest cooling power when its mounting angle is 90°, while it reaches the lowest when the mounting angle is 15°, which is 6.88% lower than that of 90°. A heat transfer stagnation zone is the main factor that affects the cooling power of the heat sink, and its location and area vary with the mounting angle. It is identified that cutting the heat transfer stagnation zone is an effective way to improve the heat sink performance.